A Novel Method for Classifying Hearing Impairment in Epidemiological Studies of Aging: The Wisconsin Age-Related Hearing Impairment Classification Scale - Cruickshanks, Karen J. (Am J Audiol, 2020)
PURPOSE: Longitudinal population-based cohort data were used to develop a standardized classification system for age-related hearing impairment using thresholds for frequencies (0.5–8 kHz) typically measured in cohort studies. METHOD: Audiometric testing data collected in the Epidemiology of Hearing Loss Study from participants (n = 1,369) with four visits (1993–1995, 1998–2000, 2003–2005, and 2009–2010) were included (10,952 audiograms). Cluster analyses (Wald's method) were used to identify audiometric patterns. Maximum allowable threshold values were defined for each cluster to create an ordered scale. Progression was defined as a two-step change. RESULTS: An eight-step scale was developed to capture audiogram shape and severity of hearing impairment. Of the 1,094 participants classified as having normal hearing based on a pure-tone average, only 25% (n = 277) were classified as Level 1 (all thresholds ≤ 20 dB HL) on the new scale, whereas 17% (n = 182) were Levels 4–6. During the 16-year follow-up, 64.9% of those at Level 1 progressed. There was little regression using this scale. CONCLUSIONS: This is the first scale developed from population-based longitudinal cohort data to capture audiogram shape across time. This simple, standardized scale is easy to apply, reduces misclassification of normal hearing, and may be a useful method for identifying risk factors for early, preclinical, age-related changes in hearing.